FAKTOR-FAKTOR YANG MEMENGARUHI MINAT PENGGUNAAN E-MONEY (Studi pada Mahasiswa STIE Ahmad Dahlan Jakarta) - Sulistyo Seti Utami; Berlianingsih Kusumawati (BALANCE: Economic, Business, Management and Accounting Journal, 2017)
ABSTRACT  The purpose of this study is to: (1) Analyze the effect of the use, convenience, and security of the interest of STIE Ahmad Dahlan Jakarta students in using e-money; (2) Analyzing the effect of e-money on the interest of STIE Ahmad Dahlan Jakarta students in using e-money; (3) Analyzing the Effect of e-money ease on the interest of STIE Ahmad Dahlan Jakarta students in using e-money; (4) Analyzing the effect of e-money security on the interest of STIE Ahmad Dahlan Jakarta students in using e-money. Type of Descriptive-Quantitative Research. The research variables consist of, X 1 = Usage X2 = Convenience, X3 = Security, Y = is interest in using e-money. Research Data is Primary Data, obtained from the results of the distribution of questionnaires designed with the scale linkert. The sample of the research was the students of STIE Ahmad Dahlan Jakarta chosen by event amounting to 100 respondents. Test Instruments using Test validity and reliability using SPSS. Technique Analysis, Multiple Regression, Classic Assumption Test, Hypothesis Test (Test F and Test t). The result showed Sig value. variable of usage (X1) 0,526> 0,05 so that H1 is rejected, e-money usage does not significantly influence student interest using e-money. It can be understood that the size of e-money does not affect students using e-money because e-money is the same with cash money (same function). Sig value. variable ease (X2) of 0.000 <from 0.05 so that H2 accepted e-money easiness significantly influence the interest of students in using e-money. The easier e-money is used, the higher the student's interest is using it. Sig value. Security (X3) is 0,036 <0,05 so that H3 accepted, e-money security influence to student interest using e-money. The higher the security of e-money then the student's interest in using e-money is higher.Keywords                   : e-Money, Usability, Convenience, SecurityCorrespondence to       : sulistyo.setiutami@gmail.com, berlianigsihkusumawati@gmail.com  ABSTRAK  Tujuan penelitian ini adalah untuk: (1) Meganalisis pengaruh kegunaan, kemudahan, dan keamanan terhadap minat mahasiswa STIE Ahmad Dahlan Jakarta dalam menggunakan e-money; (2) Menganalisis Pengaruh kegunaan e-money terhadap minat mahasiswa STIE Ahmad Dahlan Jakarta dalam menggunakan e-money; (3) Menganalisis Pengaruh kemudahan e-money terhadap minat mahasiswa STIE Ahmad Dahlan Jakarta dalam menggunakan e-money; (4) Menganalisis Pengaruh keamanan e-money terhadap minat mahasiswa STIE Ahmad Dahlan Jakarta dalam menggunakan e-money. Jenis Penelitian Deskriptif –kuantitatif . Variabel penelitian teridiri dari, X 1  = Kegunaan X2 = Kemudahan, X3 = Keamanan, Y = adalah minat menggunakan e-money. Data Penelitian adalah Data primer, diperoleh dari hasil peneyebaran kuesioner yang dirancang dengan skala linkert. Sampel Penelitian adalah mahasiswa STIE AD dipilih secara acara berjumlah 100 responden. Uji Instrumen dan Validitas Uji validitas dan reliabilitas menggunakan SPSS. Teknik Analisis, Regresi Berganda, Uji Asumsi Klasik, Uji Hipotesis (Uji F dan Uji t). Hasil penelitian menujukkan nilai Sig. variabel kegunaan (X1) 0,526 > 0,05 sehingga H1 ditolak, kegunaan e-money tidak berpengaruh secara signifikan terhadap minat mahasiswa menggunakan e-money. Hal ini bisa dipahami bahwa besar kecilnya kegunaan e-money tidak mempengaruhi mahasiswa menggunakan e-money karena kegunaan e-money sama dengan uang cash/uang tunai (fungsinya sama). Nilai Sig. variabel kemudahan (X2) sebesar 0,000 < dari 0,05 sehingga H2 diterima kemudahan e-money berpengaruh secara signifikan terhadap minat mahasiswa dalam menggunakna e-money. Semakin mudah e-money digunakan maka semakin tinggi minat mahasiswa menggunakannya. Nilai Sig. Keamanan (X3) sebesar 0,036 < 0,05 sehingga H3 diterima, keamanan e-money berpengaruh terhadap minat mahasiswa menggunakan e-money. Semakin tinggi keamanan e-money maka minat mahasiswa dalam menggunakan e-money semakin tinggi.Kata kunci                  : e-Money, Kegunaan, Kemudahan, KeamananKorespondensi             : sulistyo.setiutami@gmail.com, berlianigsihkusumawati@gmail.com